The Effect of Microlearning Integration in Digital Platforms on Student Engagement: An Experimental Study in Higher Education - Muali, Chusnul; Karlina, Lilis (Universitas Pendidikan Ganesha, 2025)
The rapid advancement of digital technology has brought about significant changes across various sectors, including the field of education. This transformation has profoundly impacted the ways in which learning materials are delivered and the interactions between educators and students, with an increasing reliance on digital platforms. This study aims to analyze the impact of integrating microlearning into digital platforms on student engagement in higher education. Microlearning integration, which breaks content into small, digestible units, is believed to enhance student participation, motivation, and retention of learning material. The study involved 80 students from three universities in Probolinggo, Indonesia. It measures the impact of microlearning through digital platforms on student engagement. The paired sample t-test analysis revealed a significant increase in engagement in the experimental group, with the average score rising from 65.4 before the intervention to 78.3 after the intervention (p < 0.05). In contrast, the control group showed no significant improvement, with the average score increasing from 64.9 before the intervention to 66.1 after (p > 0.05). These findings suggest that the use of microlearning platforms can significantly enhance student engagement. Additionally, the study provides practical recommendations for educators and institutions on integrating microlearning to create more interactive and engaging learning experiences that meet the needs of contemporary students in the digital age.